Prior knowledge of trial number influences the incidence of plateau at VO2max - Gordon, D.; Caddy, O.; Merzbach, V.; Gernigon, M.; Baker, J.; Scruton, A.; Keiller, D.; Barnes, R. (Journal of Sports Science & Medicine, 2015)
The purpose of this study was to assess the VO2max plateau response at VO2max during a series of pre-determined trials. METHODS: Ten male well-trained athletes (age, 23.0 +/- 3.2; height, 183.3 +/- 5.5 cm; mass 77.5 +/- 11.1 Kg; VO2max 66.5 +/- 5.0 ml.kg-1,min-1), but who were VO2max testing naive and with prior-knowledge of trial number completed four incremental tests to volitional exhaustion, separated by ~72-h for the deter-mination of VO2max and gas exchange threshold. Throughout all trials VO2max was recorded on a breath-by-breath basis using a pre-calibrated metabolic cart, using a plateau criterion of delta VO2 .1.5 ml.kg-1.min-1 over the final 2 consecutive 30 s sam-pling periods. A significant difference was observed between trial-1 and trial-4 for plateau incidence (p = 0.0285) rising from 20% in trial-1 to a 70% response rate in trial-4. Furthermore a significant difference was observed for VO2dif (difference be-tween criterion value and derlta VO2) in trial-1, 1.02 +/- 1.69 ml.kg-1.min-1 (p = 0.038), with non-significant differences observed for all other trials, despite a non-significant difference for VO2max across all trials (p > 0.05). Finally, a significant difference was observed for effort perception (RPE) at volitional exhaustion between trial-1 (17.7 +/- 1.3) and trial-4 (19.0 +/- 1.4) (p = 0.0052). These data indicate that prior-knowledge of trial number can influence the manifestation of the VO2 plateau in a group of well-trained male athletes, thereby suggesting that a form of effort control is established in order to preserve the finite anaer-obic capacity.